2018
DOI: 10.3390/e20120893
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Entropy Imaging of Nonalcoholic Fatty Liver Disease: Association with Metabolic Syndrome

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the leading cause of advanced liver diseases. Fat accumulation in the liver changes the hepatic microstructure and the corresponding statistics of ultrasound backscattered signals. Acoustic structure quantification (ASQ) is a typical model-based method for analyzing backscattered statistics. Shannon entropy, initially proposed in information theory, has been demonstrated as a more flexible solution for imaging and describing backscattered statistics without consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Zhou et al [22] demonstrated that entropy imaging yields a better performance than Nakagami imaging, for both liver donors and patients. Lin et al [60] compared entropy imaging with ASQ imaging and showed that entropy imaging outperforms ASQ imaging. More comparisons between different ultrasound envelope statistics parametric imaging techniques are expected in future developments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhou et al [22] demonstrated that entropy imaging yields a better performance than Nakagami imaging, for both liver donors and patients. Lin et al [60] compared entropy imaging with ASQ imaging and showed that entropy imaging outperforms ASQ imaging. More comparisons between different ultrasound envelope statistics parametric imaging techniques are expected in future developments.…”
Section: Discussionmentioning
confidence: 99%
“…A larger value of Shannon entropy indicates a greater uncertainty, representing that the ultrasound backscattered signals change from regular to random and even complex states [58]. Clinical studies demonstrated that Shannon entropy increases with increasing severity of hepatic steatosis [22,59,60]. Tsui et al [59] investigated ultrasound entropy imaging for assessing hepatic steatosis of 107 patients, using an ultrasonographic scoring system [36] as the reference standard.…”
Section: Ultrasound Entropy Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of low-quality images, numerous image processing techniques utilise information entropy as a tool for image feature extraction [ 1 ]. For instance, entropy is of great use in studying and examining the liver and other soft tissue organs [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Entropies are often used for image analysis [ 19 , 35 , 36 ]. There are two approaches for determining the structural entropy.…”
Section: Introductionmentioning
confidence: 99%